2021
DOI: 10.1088/1755-1315/869/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of sea cucumbers’s (Holothuria atra) secondary metabolite using column-chromatography technique

Abstract: Identification of sea cucumbers from Benteng Inong Balee, Aceh Besar and their phytochemistry screening were conducted in December 2020 to January 2021 at Laboratory of Marine Chemistry and Fisheries Biotechnology, Universitas Syiah Kuala. The purpose of this study was to identify the species of sea cucumbers and its secondary metabolite content using phytochemistry screening and column chromatography. The species of sea cucumbers that were identified was Holothuria atra. The extraction method used in sea cucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Sukmiwati et al (2020) supported our study where their H. atra extract from Cerocok Beach, West Sumatera, Indonesia also presented a phenolic compound without flavonoid compound. However, another part of Indonesia was found absent with phenolic compound, but flavonoid was present in their H. atra extract from a different location at Benteng Inong, Aceh Besar, and Panjang Island, Jepara (Agustina et al, 2021;Sibero et al, 2019). Esmat et al (2013) found both compounds…”
Section: Total Flavonoid and Total Phenolic Contentmentioning
confidence: 96%
See 1 more Smart Citation
“…Sukmiwati et al (2020) supported our study where their H. atra extract from Cerocok Beach, West Sumatera, Indonesia also presented a phenolic compound without flavonoid compound. However, another part of Indonesia was found absent with phenolic compound, but flavonoid was present in their H. atra extract from a different location at Benteng Inong, Aceh Besar, and Panjang Island, Jepara (Agustina et al, 2021;Sibero et al, 2019). Esmat et al (2013) found both compounds…”
Section: Total Flavonoid and Total Phenolic Contentmentioning
confidence: 96%
“…Kartikaningsih et al (2018) stated that a flavonoid test was not done since it is a phytochemical presence in plants, whereas H. atra is an animal species. Little did we know, flavonoid phytochemicals can also be found in certain animal species (Agustina et al, 2021;Rapi et al, 2020). Other than that, phenolic compounds also found ubiquitously in plants exhibit potent antioxidant activity regulated through redox properties acting as reducing agents, singlet oxygen quenchers, hydrogen donors, and metal ion chelating agents (Gulcin, 2020;Kasote et al, 2015).…”
Section: Total Flavonoid and Total Phenolic Contentmentioning
confidence: 99%
“…The change in the absorption intensity of this functional group indicates that there has been an interaction between bioactive compounds in the extract and silver solution to form silver nanoparticles. The research result by Agustina et al (2021) showed that the polyphenolic compounds contained in seacucumber extract (Holothuria atra) were flavonoids, saponins, and triterpenoids. According to Gurunathan et al (2009), hydroxide ions (OH-) play a vital role in accelerating the reduction reaction of silver ions in the formation of nanoparticles.…”
Section: Analysis Ft-irmentioning
confidence: 99%